Optical coherence tomography angiography to assess for retinal vascular changes in Neuro-Sjögren - Haar, Melanie; Konen, Franz Felix; Gehlhaar, Marten A.; Oluwatoba-Popoola, Irene; Donicova, Emilia; Wachsmann, Marija; Lubbad, Ahmed; Hufendiek, Katerina; Pielen, Amelie; Hohberger, Bettina; Mardin, Christian; Gingele, Stefan; et al. (Therapeutic Advances in Ophthalmology, 2024)
Background: Sjögren’s syndrome is an autoimmune disease characterized by sicca symptoms and various extraglandular manifestations including vasculitis. Neurological involvement occurs frequently (Neuro-Sjögren) and often mimics immune neuropathies such as chronic inflammatory demyelinating polyneuropathy (CIDP). Objectives: We aim to assess relevant differences in vessel density (VD) in Optical Coherence Tomography Angiography (OCTA) in those diseases to use it as an easily available diagnostic tool. Design: Prospective, monocentric pilot-study. Methods: OCTA (Heidelberg Engineering OCT SPECTRALIS) of the superficial vascular plexus, intermediate capillary plexus (ICP) and deep capillary plexus (DCP) of the retina was prospectively performed in Neuro-Sjögren, age-matched CIDP patients (n = 31, each), and healthy controls (n = 30). Vessel density (VD) and foveal avascular zone (FAZ) was measured with Erlangen Angio Tool. Results: Significantly lower VD were found for the DCP and ICP in Neuro-Sjögren and CIDP patients compared to healthy controls (p = 0.0002 and <0.0001). When group comparison was age-adjusted, these differences were not found anymore. Different frequencies of “low” retinal blood flow in each layer comparing Neuro-Sjögren and CIDP patients were not found. FAZ revealed no significant differences between patients with Neuro-Sjögren, CIDP and healthy controls. Conclusion: This study found no significant differences in VD or the foveal avascular zone between Neuro-Sjögren and CIDP patients using OCTA, suggesting that inflammatory vascular changes in the retina are uncommon in Neuro-Sjögren patients.
CRIS-Team Scopus Importer:2024-11-22
Keywords: chronic inflammatory demyelinating polyneuropathy; neuro-Sjögren; optical coherence tomography angiography; retinal vasculature; Sjögren’s syndrome; vasculitis